Analysis of Battery Pack Cooling System Design Using Computational Fluid Dynamics Method in Electric Vehicle - Selvia; Naryanto, Rizqi Fitri; Amrullah, Apip (Universitas Negeri Semarang, 2024)
The objective of this research is to address the heat increase in the battery, ensuring it remains below 40°C through a cooling system. Through Computational Fluid Dynamics (CFD) simulations, the impact of using Aluminium 6061, Aluminium Duralumin, and Copper, as well as the effects of cooling fluids H2O and Ethylene Glycol on the battery pack cooling system, are analyzed. Data collection is conducted using Solidworks 2022 with the Flow Simulation feature, followed by a descriptive statistical analysis to identify the optimal cooling system for the battery pack. Simulation results indicate the most optimal performance at an inlet speed of 3 m/s. For H2O, Copper maintains a temperature of 37.14°C, while Aluminium 6061 and Aluminium Duralumin reach temperatures of 37.36°C and 37.34°C, respectively. In the case of Ethylene Glycol at a speed of 3 m/s, Copper records a temperature of 194.75°C, while Aluminium 6061 and Aluminium Duralumin achieve temperatures of 197.94°C and 195.34°C, respectively. Based on this research, Copper and H2O are identified as the best choices.